The Newly Bone Formation with Carbonate Apatite-Chitosan Bone Substitute in the Rat Tibia - Anne Handrini Dewi; Andi Triawan (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
Large bone defect still represent a major problem in orthopedics. A tissue engineering approach has been proposed where osteogenic cells, bioceramic scaffolds and growth factors can play in a role to the bone repair. Bone consist a mineral phase such as carbonate apatite and an organic phase such as collagen. Synthetic carbonate apatite ceramics are considered as promising alloplastic materials for bone substitute. Chitin is the organic matrix of the hard parts of exoskeleton of insect, crustacean and present in a small amounts in mushrooms. It is an insoluble, similar to cellulose and composed of N-acetylglucosamine unit. Partial deacetylation from chitin result in the formation of chitosan. Chitin’s properties as a flexible and strong material make it favourable as surgical thread. It has novel properties such as biocompatibility, biodegradability, anti bacterial, wound healing activity, tissue regeneration and hemostatic activitities. The composit from carbonate apatite and chitosan may have a great impact on human health care system as bioresorbable bone substitute. The aim of the study was to evaluate the newly bone formation on the bone healing of defect tibia treated with carbonate apatite-chitosan bone substitute. Eighteen Sprague Dawley rats, male, 3 months, weighing 250-300g used in this study. Bilateral defect were created in each tibia rat. The defects were filled with carbonate-apatite chitosan bone substitute. The rats were sacrificed after respectively 1, 2 and 3 weeks. The result of this study showed that carbonate apatite-chitosan significantly increased a number of osteoblast (p<0.05). Carbonate apatite-chitosan group showed that matrix deposition faster than the other groups and have a good interface with the old bone. These data indicate that carbonate apatite-chitosan are potential candidate for bone substitute